First Love Sebagai Sumber Ide Perancangan Busana Pesta Formal - Hasna Khoirunisa; Ruth Ambarsari; Amin Sulistiyowati (Canthing, 2022)
The design of the end-of-duty fashion is to create a formal dress design that combines both the source of the idea and the style of dress that has been selected. The idea behind the final design of the project is the design of the formal prom fashion with the source of the first love idea-poured suga BTS through the clothes using batik and embroidered techniques as a combination of the clothes. This dress is used for formal parties. The material used in the final design of the silky cotton, lurik, and organza. The colors of the material on the final draft follow the color of the trend exploitation. Keyword: First Love